Pengaruh Motivasi dan Lingkungan Kerja terhadap Kepuasan Kerja di UKM Nahla Toys Cikampek - Firman Hidayat; Maman Suryaman; Risma Fitriani; Billy Nugraha (Universitas Bina Sarana Informatika, 2021)
This study contained two variables, namely X1 as Work Motivation and X2 as the Work Environment. This study aims to determine the influence of motivation and work environment on job satisfaction in SMEs Nahla Toys Cikampek. The Data used is primary data collected through observation, interview, distributing questionnaires and documentation. The hypothesis in this research is the influence of motivation and work environment on job satisfaction in SMEs Nahla Toys Cikampek. To measure the magnitude of influence of these variables using multiple linear regression and the help of the program software IBM SPSS 25. Based on the results of the data analysis, obtained value of the coefficient of determination amounted to 5.05%. In addition to the value of the correlation coefficient amounted to 0.711. While the results of partial test (t test) indicated that work environment variables have a significant effect on job satisfaction. It is obtained that the results of t count bigger than t table. Then based on these results it can be concluded that the work environment influence the job satisfaction of employees in SMES Nahla Toys Cikampek.